Pendampingan Manajemen Tata Kelola Madrasah di MTs. Miftahul Ulum 2 Banyuputih Kidul Lumajang - Ahmad Zarkasyi (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
This article describes Madrasah Governance Management Assistance in MTs. Miftahul Ulum 2 Banyuputih Kidul Lumajang. This research is a qualitative descriptive type with primary data sources through the role of facilitators in increasing the management capacity of madrasah governance. Researchers conducted data analysis by matching the data obtained, systematized, and interpreted logically for the sake of the validity and credibility of the data obtained by field researchers. The results of moral accreditation assistance in the form of increasing the spirit of teacher cooperation, improvement and morale, physical results are an orderly school environment and school infrastructure, administrative results in the form of an orderly school administration, and legal results in the form of an accreditation certificate with a rating of A.